2019
DOI: 10.1002/anie.201905171
|View full text |Cite
|
Sign up to set email alerts
|

New Designs for Phototherapeutic Transition Metal Complexes

Abstract: In this Minireview, we highlight recent advances in the design of transition metal complexes for photodynamic therapy (PDT) and photoactivated chemotherapy (PACT), and discuss the challenges and opportunities for the translation of such agents into clinical use. New designs for light‐activated transition metal complexes offer photoactivatable prodrugs with novel targeted mechanisms of action. Light irradiation can provide spatial and temporal control of drug activation, increasing selectivity and reducing side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
217
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(240 citation statements)
references
References 129 publications
2
217
0
2
Order By: Relevance
“…73 In PACT, light activation of an inert prodrug leads to the formation of photoproducts, which contribute to the therapeutic effects. 75,76 For example, Pt IV…”
Section: Photoactivationmentioning
confidence: 99%
“…73 In PACT, light activation of an inert prodrug leads to the formation of photoproducts, which contribute to the therapeutic effects. 75,76 For example, Pt IV…”
Section: Photoactivationmentioning
confidence: 99%
“…of the cell. [ 10 ] Ru(II), rhodium(III), or rhenium(I) complex with inert d 6 metal ions, on the other hand, are activated by photosubstitution. Under light irradiation, triplet excited states of metal‐to‐ligand character are generated, which interconvert into low‐lying triplet metal‐centered states, or d–d states.…”
Section: Self‐photoactivationmentioning
confidence: 99%
“…These excited states have strong dissociative character, which leads to ligand substitution by solvents, typically water. [ 10 ]…”
Section: Self‐photoactivationmentioning
confidence: 99%
“…With the rapid development of platinum-based anticancer complexes, several types of photoactivatable Pt(II) and Pt(IV) complexes were prepared, their modes of photoactivation were elucidated, and their antitumor effects were assessed [12]. So far, several excellent reviews have been published, which reported the development and achievement of photoactivatable platinum complexes [17][18][19]. However, no one has done a comprehensive summary on platinum drugs based on their photoactivation mechanism.…”
Section: Introductionmentioning
confidence: 99%